Association of Abnormal Renal Profiles with Subretinal Fluid in Diabetic Macular Edema - Xiaoyan Zhang; Xiaofeng Hao; Linan Wang; Like Xie (Journal of Ophthalmology)
Purpose. To investigate the risk factors for subretinal fluid (SRF) in diabetic macular edema (DME). Methods. We reviewed the records of 66 patients with DME. Systemic parameters, including hypertension, glycosylated hemoglobin, serum fasting glucose, total cholesterol, triglycerides, and diabetic kidney disease, were evaluated. Renal parameters for diabetic kidney disease included serum albumin, serum creatinine, albuminuria, and estimated glomerular filtration rate. Ocular factors included visual acuity and diabetic retinopathy, and the following parameters are evaluated through optical coherence tomography examination: disorganization of the retinal inner layers, loss of ellipsoid zone, central subretinal fluid thickness, central macular thickness, and presence of SRF. Results. Higher albuminuria (odds ratio, 3.431; 95% confidence interval, 1.039–11.334; P=0.043) was associated with the presence of SRF in patients with DME. Lower serum albumin levels (beta = −14.028, se = 6.646, P=0.044) were associated with increased SRF thickness. Conclusions. Poor kidney function was associated with the presence of SRF in DME. Screening for SRF in DME in patients with higher albuminuria and lower serum albumin levels should be routinely performed.